Interpersonal Communication Strategies Used by Sundanese Language Teachers to Create a Conductive Classroom Environment at State Senior High School 1 Sumber - Baraya Rizqy Ramadhan; Khaerudin Imawan; Welly Wihayati (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Preservation of regional languages is increasingly challenged by globalization, particularly in educational settings where communication barriers may reduce student engagement. This study aims to identify interpersonal communication strategies used by Sundanese language teachers to create a conducive classroom environment at State Senior High School 1 Sumber based on DeVito’s five dimensions of interpersonal communication: openness, empathy, support, positivity, and equality. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, participant observation, and document analysis involving one Sundanese language teacher and four grade XI students. Data validity was ensured through triangulation, member checking, and audit trails, while data were analyzed using the Miles and Huberman interactive model. Findings show that teachers apply all five dimensions contextually. Openness is demonstrated through self-disclosure to build trust. Empathy is reflected in adapting mixed-language use and understanding students’ linguistic backgrounds. Support is provided through motivation, reinforcement, and game-based learning. Positivity is created through icebreakers and constructive responses to student errors. Equality is implemented by ensuring fair participation and inclusive communication within Sundanese cultural etiquette. The integration of these interpersonal communication strategies effectively fosters a supportive and engaging learning environment while contributing to regional language preservation in broader educational context.